PENGARUH NILAI PERUSAHAAN YANG DIUKUR DENGAN MARKET TO BOOK RATIO TERHADAP STRUKTUR MODAL PERUSAHAAN (Suatu Pengujian Market Timing Theory dalam Kebijakan Struktur Modal Perusahaan) - Tia Yuliawati (Jurnal Manajemen Bisnis Performa, 2016)
The purpose of this study was to test the Market Timing Theory in the company's capital structure policy. This research was carried out in an Indonesian company in the category 50 Biggest Market Capitalization for the period 2010-2013. The method used in this research is descriptive and verification methods. The statistical method used is the method of Generalized Least Squares (GLS) with a random effect approach. The results showed that the Market Timing Theory can not explain the company's capital structure policy in Indonesia. It can be seen from the test results that prove the hypothesis that the market to book ratio has no significant effect on the capital structure.